ABH‐Glycan Microarray Characterizes ABO Subtype Antibodies: Fine Specificity of Immune Tolerance After ABO‐Incompatible Transplantation. Issue 5 (25th January 2016) - Jeyakanthan, M.; Meloncelli, P. J.; Zou, L.; Lowary, T. L.; Larsen, I.; Maier, S.; Tao, K.; Rusch, J.; Chinnock, R.; Shaw, N.; Burch, M.; Beddows, K.; et al.
Abstract : Organ transplantation from ABO blood group–incompatible (ABOi) donors requires accurate detection, effective removal and subsequent surveillance of antidonor antibodies. Because ABH antigen subtypes are expressed differently in various cells and organs, measurement of antibodies specific for the antigen subtypes in the graft is essential. Erythrocyte agglutination, the century‐old assay used clinically, does not discriminate subtype‐specific ABO antibodies and provides limited information on antibody isotypes. We designed and created an ABO‐glycan microarray and demonstrated the precise assessment of both the presence and, importantly, the absence of donor‐specific antibodies in an international study of pediatric heart transplant patients. Specific IgM, IgG, and IgA isotype antibodies to nonself ABH subtypes were detected in control participants and recipients of ABO‐compatible transplants. Conversely, in children who received ABOi transplants, antibodies specific for A subtype II and/or B subtype II antigens—the only ABH antigen subtypes expressed in heart tissue—were absent, demonstrating the fine specificity of B cell tolerance to donor/graft blood group antigens. In contrast to the hemagglutination assay, the ABO‐glycan microarray allows detailed characterization of donor‐specific antibodies necessary for effective transplant management, representing a major step forward in precise ABO antibody detection. Abstract : The authors design a novel ABH‐glycan microarray and demonstrate its effectiveness and accuracy in confirming donor‐specific B cell tolerance in a cohort of ABO‐incompatible pediatric heart transplant patients.